The Use of Internet of Things (IoT) Technology to Promote Children's Oral Health: A Scoping Review - Khafid, Moh; Bramantoro, Taufan; Hariyani, Ninuk; Setyowati, Dini; Palupi, Retno; Ariawantara, Putu Aditya Ferdian; Pratamawari, Dyah Nawang Palupi; Pindobilowo, Pindobilowo; Mohd Nor, Nor Azlida (European Journal of Dentistry, 2024)
Dental treatments and oral health promotion are now more mobile and versatile thanks to the Internet of Things (IoT)-based healthcare services. This scoping review aims to compile the available data and outline the aims, design, assessment procedures, efficacy, advantages, and disadvantages of the implementation of IoT to improve children's oral health. Articles for this review were gathered from PubMed, Scopus, and Ebscohost databases to identify and construct the keywords and primary research topic. The selected studies were published between 2000 and 2022 and focused on children aged 1 to 18 and/or parents/caregivers of children who received oral health promotion and/or dental disease preventive treatments utilizing the IoT. Each study topic required data extraction. A total of nine papers were included in this review. Two of the nine publications were quasi-experimental, while the remaining six papers were randomized control trials. The nine papers considered in this appraisal have a range of interventions and follow-up periods. Mobile-Health (m-Health), home healthcare, hospital/clinical management, and electronic-Health applications (e-Health) are the most common IoT architecture used as interventions. Three studies assessed oral health knowledge and behavior scores, whereas the bulk of studies (6/7) used m-Health treatments focusing on dental plaque buildup as well as gingival health evaluation to assess oral hygiene. IoT is one of the mediums or instruments that might be used to encourage children's dental health. The studies suggest that the use of IoT could help in improving oral hygiene and oral health, which can further improve children's oral health.
Keywords: Internet of Things (IoT); oral health promotion; telemedicine; dental health